Influence of Sintering Temperature on Phase Formation, Microstructure and Mechanical Properties of the Recycled Ceramic Body Derived from CAD/CAM Dental Zirconia Waste - Chana Sriboonpeng (Science Faculty of Chiang Mai University, 2019)
Dental zirconia (ZrO2) debris derived from computer aided design and computer aided manufacturing (CAD/CAM) waste was initially vibro-milled into nanosized ZrO2 powders prior to ceramic fabrication. The optimal pressureless sintering temperature for the production of ZrO2 ceramics was suggested via analysis of phase formation, microstructure, densification and mechanical properties results obtained from a combination of X-ray diffraction (XRD), scanning electron microscopy (SEM), Archimedes principle, Vickers hardness testing and three-point flexural strength techniques. The strength data was further analyzed using the one-way ANOVA with Scheffe post hoc test (p = 0.05) and Weibull analysis. Weibull modulus, characteristic strength and SEM characterizations were accomplished in the fracture mode. In general, it was found that no phases other than tetragonal ZrO2 were observed in the samples sintered below 1100 C whilst a coexistence of both monoclinic- and tetragonal-ZrO2 phases was found in the samples experienced higher sintering temperatures. Larger average grain sizes were observed for the samples sintered at higher temperature, whereas their porosities could be reduced resulting in an increasing of the relative density. This work demonstrated that both of physical and mechanical properties of the recycled ceramics derived from CAD/CAM dental ZrO2 waste could be significantly tailored via the choice of sintering temperature at 1100 C which provides the most comparable properties to the commercial dental ZrO2 pre-sintered block, showing the appropriation for CAD/CAM machining.